2017
DOI: 10.1177/1069072717748665
|View full text |Cite
|
Sign up to set email alerts
|

SES, Gender, and STEM Career Interests, Goals, and Actions: A Test of SCCT

Abstract: Using social cognitive career theory (SCCT), this study examined the role of socioeconomic status (SES) in an SCCT science, technology, engineering, and math (STEM) model, with gender controlled for across the model. Results showed that higher SES covaried with lower perceived career barriers, and with greater mother, father, and peer support. In turn, higher SES also predicted greater outcome expectations but not self-efficacy. Efficacy predicted STEM career interests, choice goals, and choice actions (define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 45 publications
(101 reference statements)
7
55
3
4
Order By: Relevance
“…In general, and not surprisingly, students who had STEMM career aspirations had higher math/science self-efficacy, STEMM outcome expectations, and math/science interest than those who did not have STEMM career aspirations; these results are consistent with SCCT theory as well as with research on other populations of marginalized high school students (e.g., Turner, Joeng, Sims, Dade, & Reid, 2019). Of note, however, was our finding that students with STEMM career aspirations also had higher college-going self-efficacy and college outcome expectations than students without STEMM career aspirations.…”
Section: Differences Based On Stemm Career Aspirationssupporting
confidence: 79%
See 1 more Smart Citation
“…In general, and not surprisingly, students who had STEMM career aspirations had higher math/science self-efficacy, STEMM outcome expectations, and math/science interest than those who did not have STEMM career aspirations; these results are consistent with SCCT theory as well as with research on other populations of marginalized high school students (e.g., Turner, Joeng, Sims, Dade, & Reid, 2019). Of note, however, was our finding that students with STEMM career aspirations also had higher college-going self-efficacy and college outcome expectations than students without STEMM career aspirations.…”
Section: Differences Based On Stemm Career Aspirationssupporting
confidence: 79%
“…These results are somewhat consistent with past literature, which found no differences by gender in math/science interests among low‐income PFGCSs outside of rural Appalachia (Garriott et al, 2013), as well as past findings that women have higher college self‐efficacy than do men (Gore, Leuwerke, & Turley, 2005). However, other research found that boys demonstrated higher math/science efficacy, outcome expectations, and interests than did girls (Turner et al, 2019). In addition, women are underrepresented in STEM majors in college and STEM careers beyond college (National Science Board, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…This finding is consistent with SCCT because perceived outcome expectations (e.g., college-going or immediate employment) might drive the decision-making despite readily available resources and support (e.g., close proximity to postsecondary institutions). Moreover, this finding confirms arguments that outcome expectations vary by group and career goals and actions (Turner et al, 2019). This finding suggests that, specifically for this case region and perhaps beyond, a focus on exposing students to local institutions may not be sufficient to make postsecondary enrollment seem more accessible.…”
Section: Environment-role Of Guidance Counselors and Teacherssupporting
confidence: 74%
“…Fouad and Santana (2017) claim theirs to be an exhaustive literature review. However, other sources not included therein also examine outcome expectations (e.g., Turner, Joeng, Sims, Dade, & Reid, 2019) and environmental influences (e.g., Garriott, Raque-Bogdan, Zoma, Mackie-Hernandez, & Lavin, 2017) of high school students who consider STEM careers.…”
Section: Background/frameworkmentioning
confidence: 99%
“…However, pathways into STEM careers are not only related to personal factors. Structural or social factors may work as barriers and filter out girls and women from STEM careers (Watt et al, 2006; Turner et al, 2019).…”
Section: Theory Ties Research and Practical Interventions Togethermentioning
confidence: 99%